2016
DOI: 10.1002/gps.4619
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression and resilience in older adults: a systematic review and meta‐analysis

Abstract: Few studies were found on this subject in the older population. An association between greater resilience and less depressive symptomatology was identified, albeit based on cross-sectional studies. These results highlight the need for further studies in the area and the importance of fostering the use of interventions to promote resilience in older adults as a means of preventing and managing depressive symptoms in this population. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 42 publications
8
63
0
2
Order By: Relevance
“…Psychological resilience was also found to be positively associated with happiness and satisfaction with life and negatively associated with depression among older adults (Smith & Hollinger‐Smith, ; Wagnild & Young, ). A meta‐analysis further confirmed the negative association between psychological resilience and depression among older adults (Wermelinger Avila, Lucchetti, & Lucchetti, ). Additionally, research indicated that psychological resilience was significantly associated with reduced mortality risk among the young‐old and oldest‐old in China (Shen & Zeng, ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 66%
“…Psychological resilience was also found to be positively associated with happiness and satisfaction with life and negatively associated with depression among older adults (Smith & Hollinger‐Smith, ; Wagnild & Young, ). A meta‐analysis further confirmed the negative association between psychological resilience and depression among older adults (Wermelinger Avila, Lucchetti, & Lucchetti, ). Additionally, research indicated that psychological resilience was significantly associated with reduced mortality risk among the young‐old and oldest‐old in China (Shen & Zeng, ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 66%
“…One author (RDM) assessed the quality of the included studies by using an adapted version of the Quality Assessment Tool for Quantitative Studies developed by the Effective Public Health Practice Project (Ávila, Lucchetti, & Lucchetti, 2017). This tool consists of 19 items that assess 8 criteria: (a) study design, (b) blinding, (c) representativeness -selection bias, (d) representativeness -withdrawals and dropouts, (e) confounders, (f) data collection methods, (g) data analysis, and (h) reporting.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…High scores for attributes associated with inner strength (resilience, sense of coherence, purpose and self‐transcendence) have been correlated with subjective and objective health in older adults, as has the quality of their social contact (Lundman et al., ). Studies from the USA, China and Belgium have shown an inverse relation between depression and resilience among elderly people, suggesting the importance of interventions to promote resilience to prevent and manage depression among the elderly (Wermelinger Ávila, Lucchetti, & Lucchetti, ). Many studies have also reported an association between depression and resilience as an element of inner strength (Boman, Gustafson, Häggblom, Santamäki Fischer, & Nygren, ; Lim et al., ; MacLeod, Musich, Hawkins, Alsgaard, & Wicker, ) , and it appears that older adults’ own inner strength plays a protective role against depression.…”
Section: Introductionmentioning
confidence: 99%